Facial Nerve Decompression After Temporal Bone Fracture—The Bangalore Protocol - Honnurappa, Vijayendra; Vijayendra, Vinay Kumar; Mahajan, Nilesh; Redleaf, Miriam (Frontiers in Neurology, 2019)
ABSTRACT- 187 words Background Our tertiary otology centre treats facial weakness and paralysis after motor vehicle crashes. We evaluate these patients with physical exam, audiogram, Schirmer’s test, and CT scan. Our protocol for management of the facial weakness provides good results for our patients. Methods Our protocol begins with oral steroids, and serial evaluations. Indications for decompression and our unique transcanal approach to identify the sites for decompression are described. A retrospective review of the medical record presents our patients treated between 1998-2017. Results 141 patients with grade 4 or more weakness underwent decompression. Mean pre-operative and post-operative House-Brackmann (HB) scores were HB5 and HB2 respectively. Fourteen of 104 patients (13%) presenting with HB5 and 6 still had HB5 or HB6 after decompression. Eighty-three of the 104 patients (80%) achieved HB1 or HB2 at 6 months. Post-operative bone levels were unchanged. Post-operative air levels were improved in cases of perigeniculate fractures (84%). Conclusion This Bangalore protocol facilitates advantageous improvement in facial function and conductive hearing loss after traumatic facial nerve crush injuries. The surgical technique, albeit challenging, helps identify the fracture lines, facilitates reconstruction of disrupted ossicles, and avoids craniotomy.